THE LEGACY OF THE DISINHERITED: POPULAR CULTURE IN LATIN AMERICA: MODERNITY, GLOBALIZATION, HIBRIDITY AND AUTHENTICITY - Salman, Ton (edición) (CEDLA LATIN AMERICAN STUDIES SERIES;, 1996)
INCLUYE BIBLIOGRAFIA